2003
DOI: 10.1002/bies.10230
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillar collagen: The key to vertebrate evolution? A tale of molecular incest

Abstract: Fibril-forming (fibrillar) collagens are extracellular matrix proteins conserved in all multicellular animals. Vertebrate members of the fibrillar collagen family are essential for the formation of bone and teeth, tissues that characterise vertebrates. The potential role played by fibrillar collagens in vertebrate evolution has not been considered previously largely because the family has been around since the sponge and it was unclear precisely how and when those particular members now found in vertebrates fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
133
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 31 publications
6
133
0
Order By: Relevance
“…5 for exon structures through these domains). These unusual molecular features of the collagen XXVII polypeptide have previously only been found in invertebrate fibrillar collagens (7). However, in type XXVII, these features appear to have evolved within the vertebrate lineage after the type C clade diverged from the type B clade (Fig.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…5 for exon structures through these domains). These unusual molecular features of the collagen XXVII polypeptide have previously only been found in invertebrate fibrillar collagens (7). However, in type XXVII, these features appear to have evolved within the vertebrate lineage after the type C clade diverged from the type B clade (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…The founder vertebrate fibrillar collagen gene acquired an elongated chain selection sequence (7). Gene/genome duplication events led to the evolution of the founder genes for the type A, B, and C clades.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…In vertebrates, a short region of the C-propeptide appears to be involved in chain recognition (3). Recently, Boot-Handford and Tuckwell (4) indicated that most of this recognition sequence is absent in all invertebrate fibrillar chains characterized to date. During the extracellular maturation of procollagen molecules, the propeptides are generally removed by specific proteinases.…”
mentioning
confidence: 99%